Arthroscopic Versus Open Stabilization for Anterior Shoulder Subluxations. Issue 1 (23rd January 2015) - Owens, Brett D.; Cameron, Kenneth L.; Peck, Karen Y.; DeBerardino, Thomas M.; Nelson, Bradley J.; Taylor, Dean C.; Tenuta, Joachim; Svoboda, Steven J.
Background: Most of the literature on shoulder instability focuses on patients experiencing anterior glenohumeral dislocation, with little known about the treatment of anterior subluxation events. Purpose: To determine the outcomes of surgical stabilization of patients with anterior glenohumeral subluxations and to compare open and arthroscopic approaches. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: We prospectively enrolled patients with anterior glenohumeral subluxations undergoing surgical stabilization. Patients were offered randomization between open and arthroscopic stabilization. Inclusion criteria included patients with anterior glenohumeral subluxations undergoing Bankart repair, while exclusions included the presence of glenoid or humeral bone loss, multidirectional instability, capsular tear/humeral avulsion of the glenohumeral ligament lesion, and rotator cuff tear requiring repair. Patients were randomized to an open Bankart repair through a subscapularis takedown or an arthroscopic Bankart repair, both using the same bioabsorbable suture anchors, and they were followed for a minimum of 2 years. Outcomes were evaluated with the Single Assessment Numeric Evaluation (SANE), Western Ontario Shoulder Instability Index (WOSI), American Shoulder and Elbow Surgeons Score (ASES), Simple Shoulder Test (SST), Rowe, and Tegner activity scores. Results: A total of 26 patients were enrolled, with 7 being lost to follow-up. Complete follow-up data were available on 19 subjects (74%): 10 in the open group and 9 in the arthroscopic group. There were no significant differences noted between the randomized groups, with a 2-year WOSI score of 320 in the open subjects and 330 in the arthroscopic subjects, and similar findings in the other scoring scales. There were no cases of dislocation following surgery. There were 3 patients with recurrent instability (subluxations only) in each group at a mean of 17 months, for an overall recurrent subluxation rate of 31%. These subjects with recurrence had lower outcome scores (WOSI, 532; SANE, 88.4). The outcomes of the 9 subjects with ≤3 subluxation events were superior to those of the 10 subjects with >3 events prior to stabilization. The patients with ≤3 events had a WOSI score of 143, compared with 470 ( P = .042), and an ASES mean score of 98.8, compared with 87.1 ( P = .048). Four of the 6 patients with recurrent subluxations had sustained >3 subluxations prior to stabilization. Conclusion: Overall, patients with Bankart lesions resulting from an anterior glenohumeral subluxation event had excellent outcomes with surgical stabilization. The overall recurrence in the 19 subjects with at least 2-year follow-up was 6 cases (31%), with no instances of dislocation in this young, active cohort. There was no significant benefit to open or arthroscopic stabilization, and we did find that stabilization of subluxation patients with ≤3 events resulted in superior outcomes compared with chronic recurrent subluxation patients with >3 events. We recommend early surgical stabilization of young athletes with Bankart lesions that result from anterior subluxation events.